A standardized ultrasound approach to pelvic congestion syndrome. (October 2017) - Labropoulos, Nicos; Jasinski, Patrick T.; Adrahtas, Demetri; Gasparis, Antonios P.; Meissner, Mark H.
Pelvic congestion syndrome is one of the many causes of chronic pelvic pain and is often diagnosed based on exclusion of other pathologies. Over the past decades, pelvic congestion syndrome was recognized to be a more common cause of chronic pelvic pain. Multiple diagnostic modalities including pelvic duplex ultrasonography, transvaginal ultrasonography, computed tomography, and magnetic resonance were studied. In the current literature, selective ovarian venography, an invasive imaging approach, is believed to be the gold standard for diagnosing pelvic congestion syndrome.